Modelling CO₂ transport and the effect of impurities: a new equation of state for CCS pipeline transport - Demetriades, Thomas A. (2014)
In this EngD project I developed a new, analytic equation of state for use in the area of CCS pipeline transport. It was my aim to design a model which would exhibit a high degree of accuracy within the anticipated window of operation of CCS pipelines; from 260 to 335K and 1 to 200bar, whilst simultaneously retaining a simplicity and ease-of-use, a lack of which made some other available equations particularly unwieldy. Having conducted a comprehensive literature review and attended many academic and industrial conferences throughout this project, I felt that there was a need for an equation of state which could perform both these functions. This was the key motivation for my work, and the model presented in this thesis was developed in order that it might contribute towards negating the many concerns that currently surround the pipeline transport stage of CCS. I aimed for the proposed model to display a complexity approaching that of some of the simpler equations currently available, whilst incorporating sucient flexibility to give thermodynamic predictions to a standard approaching that of those which are more complicated. I defined criteria by which the proposed model could be judged, so that it could be applied with condence in the determination of the physical properties of carbon dioxide mixtures during CCS pipeline transport. Work was carried out by fitting the parameters of the proposed model to experimental data gathered from the literature, so that it would be able to determine the homogeneous phase pressure and vapour-liquid equilibrium behaviour of carbon dioxide and other relevant gas mixtures. The project yielded a number of excellent outputs, not least the satisfaction of the primary aim which was the proposal of a model, which through this EngD, I demonstrated had the ability to meet the demands that were set. In carrying out this work, I also developed several highly useful auxiliary mathematical methods which helped in ensuring the proposed model was as accurate as possible. For the case of modelling pure carbon dioxide, the proposed equation worked exceptionally well, providing highly accurate predictions for homogeneous density and vapour liquid equilibrium, which were well within the targets set. A paper on this was published in May 2013. In extending the model to incorporate some binary mixtures I again found that it demonstrated a clear ability to capture the necessary physical behaviours within the target range. I concluded with suggestions as to ways in which the work presented here could be developed further, as well as the many avenues for future work in other areas that this EngD project had opened up.